What Drives the Interest Rate Margin Decline in EU Banking – The Case of Small Local Banks - David Liebeg; Markus S. Schwaiger (Kredit und Kapital, 2009)
What Drives the Interest Rate Margin Decline in EU Banking – The Case of Small Local Banks Bank interest rate margins have been declining in most EU countries over the last decade. This paper investigates the determinants of bank interest rate margins drawing on a unique sample of small local banks in Austria. The reduction of small local banks interest rate margins is mainly driven by a combination of decreasing operating costs, enabling banks to charge lower margins, and increasing competition. In addition, there seems to be a tradeoff between small local banks margins and non-interest revenues. In contrast to findings in the literature we furthermore document a small, but significantly positive effect of relationship banking on interest rate margins. (JEL G21, E40, C33) – – Die Determinanten der Zinsspannenreduktion auf dem EU-Bankenmarkt am Beispiel kleiner Lokalbanken Im letzten Jahrzehnt sind die Zinsspannen von Banken in den meisten Märkten der EU zurückgegangen. Dieser Aufsatz untersucht die Determinanten von Zinsspannen am Beispiel kleiner Lokalbanken in Österreich. Der Rückgang der Zinsspannen wird vor allem durch einen Rückgang der Kosten und eine Steigerung des Wettbewerbs getrieben. Zudem scheinen niedrigere Zinsspannen durch höhere Erträge im Nicht-Zinsgeschäft kompensiert zu werden. Im Gegensatz zu bisherigen Ergebnissen aus der Literatur existiert ein positiver Zusammenhang zwischen der Bedeutung des Hausbankenprinzips und der Zinsspanne.
Keywords: G21; E40; C33; 330